2023
DOI: 10.3390/fermentation9020180
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Wheat Straw Conversion into Microbial Lipids by Lipomyces tetrasporus DSM 70314 from Bench to Pilot Scale

Abstract: Microbial lipids are renewable platforms for several applications including biofuels, green chemicals, and nutraceuticals that can be produced from several residual carbon sources. Lignocellulosic biomasses are abundant raw materials for the production of second-generation sugars with conversion yields depending on the quality of the hydrolysates and the metabolic efficiency of the microorganisms. In the present work, wheat straw pre-treated by steam explosion and enzymatically hydrolysed was converted into mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…Unfavorable culture conditions can activate survival mechanisms, leading to inhibition of anabolic processes like protein synthesis 19 . Therefore, optimizing culture conditions using statistical tools is a common practice to enhance the production of SCP and biomass in various microorganisms 24 . In our initial study, we demonstrated the effective reuse of CWW for SCP production using the design of experiments (DoE) technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfavorable culture conditions can activate survival mechanisms, leading to inhibition of anabolic processes like protein synthesis 19 . Therefore, optimizing culture conditions using statistical tools is a common practice to enhance the production of SCP and biomass in various microorganisms 24 . In our initial study, we demonstrated the effective reuse of CWW for SCP production using the design of experiments (DoE) technique.…”
Section: Introductionmentioning
confidence: 99%
“…19 Therefore, optimizing culture conditions using statistical tools is a common practice to enhance the production of SCP and biomass in various microorganisms. 24 In our initial study, we demonstrated the effective reuse of CWW for SCP production using the design of experiments (DoE) technique. The culture process was established in a medium containing 87.5% (v/v) CWW, along with 1.38 g/L of yeast extract, and 7.24 g/L of ammonium sulfate [(NH 4 ) 2 SO 4 ], resulting in a high SCP yield of approximately 38%.…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to its ability to not only bypass competition with food production for sugar/starch feedstocks but also to alleviate disruptions to soil microorganisms caused by the direct combustion of agricultural residues [7,8]. During the process, the second-generation sugars obtained by the hydrolysis of lignocellulosic biomass can also be used to produce a wide range of bioproducts [9].…”
Section: Introductionmentioning
confidence: 99%
“…This practice releases toxic pollutants in the environment and causes health problems in human beings. Therefore, the utilization of lignocellulosic biomass as a substrate for the cultivation of microorganisms is preferred for the production of bioacetoin at the industrial level [8,11,14]. Lignocellulosic biomass is a complex structure composed of cellulose, hemicellulose and lignin, which are hydrolysed into monomers for the production of valuable products, including biofuels, biopolymers, biopesticides, etc., using microorganisms [2,4,9,13,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Physico-chemical methods of pretreatment have been preferred due to high lignin removal and improved enzymatic hydrolysis. Usually, the biomass is pretreated to disrupt its complex and recalcitrant nature, thus resulting in the release of carbohydrates or sugars that are utilized by microorganisms for the production of bioacetoin [13,14,[16][17][18]. But there is a need for ample supply of the respective biomass with simple processing for effective utilization at the industrial scale.…”
Section: Introductionmentioning
confidence: 99%